3 m × 3 m heterolithic passive resonant gyroscope with cavity length stabilization. (7th October 2020) - Zhang, Fenglei; Liu, Kui; Li, Zongyang; Feng, Xiaohua; Li, Ke; Ye, Yanxia; Sun, Yunlong; He, Leilei; Schreiber, K Ulrich; Luo, Jun; Lu, Zehuang; Zhang, Jie
Abstract: Large-scale high sensitivity laser gyroscopes have important applications for ground-based and space-based gravitational wave detection. We report on the development of a 3 m × 3 m heterolithic passive resonant gyroscope (HUST-1) which is installed on the ground of a cave laboratory. We operate the HUST-1 on different longitudinal cavity modes and the rotation sensitivity reaches 1.6 × 10 −9 rad s −1 Hz −1/2 above 1 Hz. The drift of the cavity length is one of the major sensitivity limits for our gyroscope in the low frequency regime. By locking cavity length to an ultra-stable reference laser, we achieve a cavity length stability of 5.6 × 10 −9 m Hz −1/2 at 0.1 mHz, a four orders of magnitude improvement over the unconstrained cavity in the low frequency regime. We stabilize the cavity length of a large-scale heterolithic passive resonant gyroscope through active feedback and realize long-term operation. The rotation sensitivity reaches 1.7 × 10 −7 rad s −1 Hz −1/2 at 0.1 mHz, a three orders of magnitude improvement over the unconstrained cavity, which is no longer limited by the cavity length drift in this frequency range.